Why is Generation Z Prone to Swearing?: A Psycholinguistic Study on Semantic Shifts in Profanity (Mengapa Generasi Z Mudah Mengumpat?: Studi Psikolinguistik pada Perubahan Semantik dalam Umpatan) - Sigit Nugroho; Ersaliyah Arezah; Muhammad Ahkam Alwi; Wahyudi Rahmat; Lisfarika Napitupulu; Yanwar Arief (Universitas PGRI Sumatera Barat, 2023)
Humans often use profanity as verbal aggression to express displeasure towards others or a particular situation. Using animal names and gender-related terms with regional connotations is common in Indonesian society. Generation Z, who predominantly engage in social media, have learned to use words like animal names or genders as tools to express their emotions, both aggressively and non-aggressively, which impact on interpersonal communication. This research aims to understand the semantic changes of words created by Generation Z. This will be achieved by applying four principles of semantic change: amelioration, pejoration, narrowing, and broadening. This research will explore the use of expletives in the style of Generation Z in their daily lives and the purpose behind their usage. The study adopts a qualitative approach, with eight respondents meeting the criteria of being part of Generation Z, frequently using expletives, and actively participating in social media. The data obtained will be analyzed using a thematic approach. The results of this study indicate that the expletives used by Generation Z have deviated from standard literal language. Despite undergoing semantic changes, the words coined by Generation Z still constitute a part of verbal aggression. The inability to contextualize expletives within normative, psychological, and sociological perspectives renders these words commonplace and acceptable.